2019
DOI: 10.3390/agronomy9090554
|View full text |Cite
|
Sign up to set email alerts
|

Leguminous Cover Crop Astragalus sinicus Enhances Grain Yields and Nitrogen Use Efficiency through Increased Tillering in an Intensive Double-Cropping Rice System in Southern China

Abstract: Chinese milk vetch (Astragalus sinicus L., vetch), a leguminous winter cover crop, has been widely adopted by farmers in southern China to boost yield of the succeeding rice crop. However, the effects of vetch on rice grain yield and nitrogen (N) use efficiency have not yet been well studied in the intensive double-cropped rice cropping systems. To fill this gap, we conducted a three-year field experiment to evaluate the impacts of the vetch crop on yields and N use efficiency in the subsequent early and late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Crops followed by legume rotations usually showed promoted nitrogen accumulation and higher grain yields (Yu et al 2014;Zhu et al 2016). Sometimes, yield reduction of the main crop resulted from rotation could be attributed to the competition for nitrogen after the incorporation of the second crop residue, such as rape and ryegrass because of a high carbon/nitrogen ratio (Armstrong et al 1996;Nie et al 2019), in spite that the rotation treatments were coupled with crop residue return, which means an additional nitrogen supply during the main rice crop season (Zhu et al 2016). In this study, rotation with wheat or with rape had no significant effect on the grain yield and above ground biomass of rice for both years, possibly due to the high level of rice grain yields (ranged from 12.1 to 13.6 t ha -1 , Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crops followed by legume rotations usually showed promoted nitrogen accumulation and higher grain yields (Yu et al 2014;Zhu et al 2016). Sometimes, yield reduction of the main crop resulted from rotation could be attributed to the competition for nitrogen after the incorporation of the second crop residue, such as rape and ryegrass because of a high carbon/nitrogen ratio (Armstrong et al 1996;Nie et al 2019), in spite that the rotation treatments were coupled with crop residue return, which means an additional nitrogen supply during the main rice crop season (Zhu et al 2016). In this study, rotation with wheat or with rape had no significant effect on the grain yield and above ground biomass of rice for both years, possibly due to the high level of rice grain yields (ranged from 12.1 to 13.6 t ha -1 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has confirmed that rotation in paddy cropping systems, especially those with legumes could play an important role in promoting nutrient cycling, improving soil fertility and maintaining food production by reducing fertilizer investment (Nie et al 2019). The release of environmental hazard compounds such as NO 3 leaching and N 2 O emission from farmland could also be reduced by rotation (Yu et al 2014;Machado et al 2021), or by replacing winter fallow with cover crops (Zhu et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Five treatments were set: N0 (without N), N1 (urea), N2 (ammonium sulfate), N3 (ammonium nitrate) and N4 (sodium nitrate). Pure N applied in each pot was 1.62 g, equal to 180 kg/hm 2 . In order to ensure the stability of N fertilizer, 5% nitrogenous nitrification inhibitor dicyandiamide was added in all treatments.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…South China locates in the tropical and subtropical regions, rich in water and heat resources. Rice can be planted several times in the area within one year [2]. To achieve better yield and quality, rice growers have applied large amounts of nitrogen (N) fertilizer in different seasons of rice production.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a winter cover crop of Chinese milk vetch (Astragalus sinicus L.) on subsequent double-cropped rice in southern China is discussed in the article by Nie et al [45]. Under moderate and high N input, they found that a Chinese milk vetch cover crop increased grain yield of the early and late rice crops compared to no cover crop, largely due to increased tillering.…”
Section: Cover Cropsmentioning
confidence: 99%